Online Audiences and Gatekeeping: User Comments and Their Influence on Editorial Processes in Newsrooms in Kenya - Beryl Anyango Oywer; Nancy Booker; Hesbon Hansen Owilla; Paul Kimweli (European Scientific Journal, ESJ, 2023)
In Kenyan newsrooms, there has been a debate about keeping the comment section on news websites in the aftermath of Social Media Networks. This allows the media to still collect user opinions without the risk of unregulated third-party comments. This paper sought to establish the nature and influence user comments have on editorial processes and explain what value media houses that have retained the comment section are receiving. To investigate this, the researchers adopted mixed methods research approach (quantitative and qualitative) and concurrent mixed methods research designs. The targeted population was journalists working in media houses that operate in print, broadcast, and digital news websites in Nairobi County. The targeted media houses were: Nation Media Group (NMG), Standard Group (SG), and Radio Africa Group (RAG). The sample size comprised 252 participants for quantitative data, nine key informants for in-depth interviews, and 84 articles for direct content analysis. Surveys and directed content analysis were used as strategies of inquiry. These strategies were aided by questionnaires, in-depth interviews, and code sheets as data generation tools.   Statistical Package for Social Sciences (IBM/SPSS) was used to analyse quantitative data. Quantitative data was presented using tables and pie charts. Qualitative data was thematically analysed and presented in the form of themes. Contrary to popular belief, the findings show that discussions in news website comment sections are frequently marred by incivility. Instead, most of the comments were deliberative, with audience members just looking for a forum to express themselves civilly. However, in cases with reported incidences of incivility, the sources quoted were the main trigger. Journalists have been shown to use user input in the comment section to gauge the quality of their content, while media companies use audience knowledge to make strategic decisions. The results shed light on how newsrooms may give the public a platform to discuss and give their input on the news while maintaining deliberative debates.